A mathematical model of Noggin and BMP densities in adult neural stem cells. Issue 1 (1st January 2017) - Larripa, Kamila; Gallegos, Angela
Abstract: New neurons are generated in the adult hippocampus throughout life by neural stem cells (NSCs) in a dynamic process responsive to external signalling cues. NSCs in the adult hippocampus divide infrequently, and it has been shown that bone morphogenetic protein (BMP) modulates their quiescence. Infusion of Noggin, a BMP antagonist, blocks this signalling. We investigate the balance of BMP and Noggin in this particular niche and qualitatively reproduce experimental results obtained and qualitatively reproduce experimental results with a one-dimensional reaction–diffusion model. We use the model to connect BMP signalling profiles with specific cellular outcomes and to determine whether the transient infusion of BMP leads to a signalling profile which can be reversed by the infusion of Noggin. Additionally, we analyse the role of diffusion in this system for generating signalling profiles with dramatically different cell-fate outcomes and show that diffusion-driven instability is not possible in our system of reaction–diffusion equations.